2015
DOI: 10.3892/or.2015.3938
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1-mediated downregulation of uPA and MMP9 by 3,3′-diindolylmethane inhibits migration and invasion of human colorectal cancer cells

Abstract: Although 3,3'-diindolylmethane (DIM) has been suggested to reduce the risk of colorectal cancer, the underlying biological mechanism is not clearly understood. In the present study, we investigated the effect of DIM on the migratory and invasive activities of the human colorectal cancer cell lines DLD-1 and HCT116. DIM significantly inhibited the migration and invasion of colorectal cancer cells as assessed by wound healing and Matrigel invasion assays. The migratory ability of the DLD-1 and HCT116 cells was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“… 23 Upregulated FOXM1 expression and enhanced FOXM1 activity facilitate penetration of the basement membrane by malignant tumor cells, which can then spread to other tissues. 24 The above studies have indicated the important role of FOXM1 in the proliferation, invasion, and metastasis of malignant cells, factors that affect cancer patient prognosis.…”
Section: Discussionmentioning
confidence: 98%
“… 23 Upregulated FOXM1 expression and enhanced FOXM1 activity facilitate penetration of the basement membrane by malignant tumor cells, which can then spread to other tissues. 24 The above studies have indicated the important role of FOXM1 in the proliferation, invasion, and metastasis of malignant cells, factors that affect cancer patient prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, we found that DIM significantly downregulates β-catenin and c-Myc signaling to inhibit colon cancer cell growth ( Figure 2 ) [ 62 ]. Another study conducted by our laboratory showed that DIM significantly represses the migration and invasion of colorectal cancer cells (DLD-1 and HCT-116) [ 63 ]. We found that mRNA levels of urokinase type plasminogen activator (uPA) and matrix metalloproteinase ( MMP )-9 were decreased, and that of E-cadherin were increased.…”
Section: 33′-diindolylmethane and Colorectal Cancermentioning
confidence: 99%
“…We found that mRNA levels of urokinase type plasminogen activator (uPA) and matrix metalloproteinase ( MMP )-9 were decreased, and that of E-cadherin were increased. These mRNA levels are mediated by reduced mRNA and protein levels of FOXM1, indicating that DIM inhibits migration and invasion by inactivating FOXM1 [ 63 ]. In another study, we found that DIM enhances the toxicity of LY294002, a PI3K inhibitor, in colon cancer cells, as demonstrated by the results of a cell-viability assay, clonogenic assay, and immunoblotting analysis of apoptotic markers [ 28 ].…”
Section: 33′-diindolylmethane and Colorectal Cancermentioning
confidence: 99%
“…The overexpression of FOXM1 expression or activity has been associated with the occurrence and development of numerous types of cancer (14)(15)(16)(17). Activation of FOXM1, as an independent poor prognostic factor, is associated with the proliferation and metastasis of human colon cancer cells, and decreased overall survival and metastasis-free survival rates in patients with CRC (18).…”
Section: Discussionmentioning
confidence: 99%